The effect of rice hull as a silicon source on anthracnose disease resistance and some growth and fruit parameters of capsicum grown in simplified hydroponics - Ruwani Kalpana Jayawardana; Darshani Weerahewa; Janakie Saparamadu (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Introduction Silicon is beneficial for many plants for growth, yield and enhancing resistance to biotic and abiotic stresses. In the present study, silicon as a form of rice hull sand mixture (3:2 v/v) was used in simplified hydroponic system to evaluate the performance and disease resistance of Capsicum annuum L. The nutrients were supplied by NF (New Formula) or Albertâs solution. Results Continuous monitoring of soluble silicon content in the simplified hydroponic boxes revealed that a high amount of silicon was leached by the rice hull sand medium. Disease resistance was assessed by challenge inoculation of harvested fruits with anthracnose-causing fungi, Colletotrichum gloeosporioides, and it was observed a significant disease reduction (over 83 %) in fruits harvested from simplified hydroponic system compared to that of liquid hydroponic system. Shoot length, root length, fruit length, fruit weight and fruit firmness were also increased significantly in simplified system compared to the liquid system. However, the results were not significantly affected by the nutrient solutions used in these two systems. Conclusions In conclusion, the simplified hydroponic system composed of rice hull, as a natural silicon supplement could be used as a low-cost environmental friendly growing method of capsicum to enhance resistance against anthracnose disease, and to improve plant growth and fruit quality.